Exploration on the effect of anserine on the alleviation of DVT and its molecular mechanism - Li, Yan; Ge, Jingping; Yin, Yuanyuan; He, Juan; Shang, Longcheng (Frontiers in Pharmacology, 2024)
Background This study aimed to explore the regulatory effect of anserine on HUVEC cell injury and thrombosis in deep venous thrombosis (DVT) rats, and to elucidate the underlying molecular mechanisms. Methods Non-targeted metabolomics data analyses were conducted using an ultra-performance liquid chromatography system Vanquish UHPLC and mass spectrometer to detect plasma metabolism profiles. The transcriptome sequencing and gene intervention experiments were performed to verify the regulatory effect. Further in vivo and in vitro experiments were performed. Enzyme-linked immunosorbent assay was used to detect the levels of P-selectin, E-selectin, and vWF, hematoxylin-eosin (HE) staining was performed to observe thrombotic and inflammatory cell infiltration, flow cytometry and TUNEL assays were performed to detect apoptosis, and qPCR and WB assays were conducted to determine the gene and protein expression. Results Anserine alleviated HUVECs injury, reduced adhesion molecule expression, and inflammation. It decreased P-selectin, E-selectin, vWF, THBD, TFPI levels, and apoptosis while promoting NOS3, ET-1, and NO release in HUVECs. In DVT rats, anserine reduced P-selectin, E-selectin, vWF, thrombosis, cell infiltration, apoptosis, and promoted NO release. Transcriptome sequencing and gene intervention confirmed anserine’s regulation of the PI3K-Akt pathway and coagulation via MYB. CARNMT1, a regulatory enzyme for anserine metabolism, increased anserine content, inhibiting coagulation, thrombosis, cell infiltration, and promoting NO release in rats. Conclusion This study confirmed anserine could alleviate DVT by improving the inflammatory response, inhibiting blood agglutination, and promoting vasodilation, providing new potential therapeutic targets, important scientific evidence for the development of DVT management, and new clues for an in-depth understanding of its molecular mechanisms.